Preliminary study on conjugation of formononetin with multiwalled carbon nanotubes for inducing apoptosis via ROS production in HeLa cells - Guo B; Liao C; Liu X; Yi J (Dove Medical Press, 2018)
Bohong Guo, Cancheng Liao, Xiaohong Liu, Jun Yi Department of Pharmaceutics, Guangdong Pharmaceutical University, Guangzhou, China Background: The present work was conducted to prepare and evaluate multiwalled carbon nanotube–formononetin (MWCNT-FMN) composite for sustained delivery and inducing apoptosis via reactive oxygen species (ROS) production in HeLa cells.Methods: The composite was prepared by solution mixing with short carboxylic group-functionalized multiwalled carbon nanotubes (MWCNT-COOH). Then the composite was characterized by laser particle size analysis, Fourier transform infrared spectrometry, X-ray diffractometry, differential scanning calorimetry, and scanning electron microscopy. Drug release rates in vitro were determined by dialysis method. The in vitro cytotoxicity study was performed using water soluble tetrazolium assay. The cellular apoptosis assay, ROS, and mitochondrial membrane potential (MMP) of HeLa cells were investigated by acridine orange and ethidium bromide double dye, 2',7'-dichlorodihydrofluorescein diacetate, and 5,5',6,6'-tetrachloro-1,1',3,3'-tetraethyl-imidacarbocyanine iodide probe, respectively.Results: The entrapment efficiency was 28.77%±0.15%, and the loading capacity was 12.05%±0.20%. The release of MWCNT-FMN was sustained, and the cumulative release rate of formononetin (FMN) from MWCNT-COOH was higher at pH 7.4 than at pH 5.3. The in vitro cytotoxicity assay demonstrated that FMN, MWCNT-COOH, and MWCNT-FMN had no significant effects on the proliferation and viability of mouse fibroblast 3T3 cells over 48 hours, while the cell growth inhibition of the three samples showed concentration-dependent for HeLa cells. Biological assay suggested FMN and MWCNT-FMN could induce apoptosis in HeLa cells, meanwhile the cells exhibited stronger ROS signal and more depolarized MMP than that of the control group.Conclusion: These results preliminarily demonstrated that MWCNT-FMN exerted anticancer efficacy through cellular apoptosis induced by ROS-mediated mitochondrial dysfunctions in HeLa cells. Keywords: multiwalled carbon nanotube, characterization, cytotoxicity, formononetin, apoptosis